Shanghai: a (Self) Portrait - Piazzoni, Maria Francesca; Basso, Matteo (Journal of Architecture and Urbanism, 2017)
Editorial. Shanghai: a (Self)Portrait Journal of Architecture and Urbanism, 41(2), pp. 79–81